Spatially homogeneous bianchi type-V cosmological model with early deceleration and late-time acceleration - Ram S.; Chandel S.; Verma M.K. (My University, 2025)
We have studied a spatially homogeneous and anisotropic cosmological model of Bianchi type -V filled with a perfect uid in scale-covariant theory of gravitation. Exact solutions of the field equations are presented by using a special form of the deceleration parameter which gives an early decelerating and late time accelerating cosmological model. The gravitational constant G is assumed proportional to the square of the average scale factor of the model. The anisotropic model approaches isotropy and tends to de -Sitter universe at late times. The geometrical and physical aspect of the model are also studied. The model is consistent with recent observations.